2023
DOI: 10.1007/s10461-023-03988-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on HIV Care in Rio de Janeiro, Brazil 2019–2021: Disparities by Age and Gender

Abstract: We evaluated COVID-19’s impact on HIV care indicators among INI/FIOCRUZ’s HIV Clinical Cohort in Rio de Janeiro, Brazil: (1) Adequate care visits: two visits ≥ 90 days apart; (2) Adequate viral load monitoring: ≥ 2 viral load results ≥ 90 days apart; (3) Consistent viral suppression: all viral loads < 40 copies/mL; and (4) ART medication possession ratio (MPR) ≥ 95%. Chi-square tests compared the fraction of participants meeting each indicator per period: pre-pandemic (3/1/2019–2/29/2020) and post-pandemic (3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
(66 reference statements)
0
9
0
Order By: Relevance
“… 27 , 36 Among TGW living with HIV, studies have shown that this population has lower linkage to care, lower use of ART, and poorer adherence to clinical visits. 37 , 38 For TGW, barriers to accessing care include transphobia, stigma, socioeconomic instability, and lack of awareness of available services. 26 Importantly, recent experience at INI/Fiocruz has shown that providing a welcoming, gender-affirming environment with gender-neutral toilets and trans-affirming posters, for example, can improve outcomes for TGW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 36 Among TGW living with HIV, studies have shown that this population has lower linkage to care, lower use of ART, and poorer adherence to clinical visits. 37 , 38 For TGW, barriers to accessing care include transphobia, stigma, socioeconomic instability, and lack of awareness of available services. 26 Importantly, recent experience at INI/Fiocruz has shown that providing a welcoming, gender-affirming environment with gender-neutral toilets and trans-affirming posters, for example, can improve outcomes for TGW.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent analysis evaluating continuum of care outcomes before and during the COVID-19 pandemic showed that COVID-19 disrupted care access disproportionately for TGW. 46 HIV services for TGW in Brazil should emphasize gender-affirmative care, promote autonomy, and include population-specific peer programming. 47 INI/Fiocruz has actively addressed barriers to engagement in care among TGW by enabling the establishment of Transcendendo , the first trans-specific cohort in a low- or middle-income country, and facilitating the inclusion of TGW in research studies.…”
Section: Discussionmentioning
confidence: 99%
“…The INI-Fiocruz cohort is a longitudinal observational clinical cohort with PWH receiving HIV care since 1986, as described elsewhere. 13 , 14 , 15 , 16 For this study, inclusion criteria were: (1) Age 50-years or older at the day of assessment, (2) Confirmed HIV infection, (3) Currently using antiretroviral therapy. Exclusion criteria were: (1) Participants with Parkinson disease; (2) MINI-Mental State Examination (MMSE) score <18 points; (3) Any clinical condition that impaired participation and compliance with study procedures.…”
Section: Methodsmentioning
confidence: 99%
“… 13 Moreover, the COVID-19 pandemic disrupted access to the HIV care continuum for PWH in this cohort, such as adequate care visits, viral load monitoring, and optimal medication possession ratio. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the country's longstanding commitment to universal access to antiretroviral therapy (ART), structural barriers remain, resulting in a high prevalence of HIV late presentation to care and poor ART adherence. These aspects have worsened after the COVID-19 pandemic and contributed to the high mpox burden [24][25][26].…”
Section: Introductionmentioning
confidence: 99%